Behind 'The Last Door': Prison Managers' Experiences of Accountability and Oversight - Curristan, Sarah (Trinity College Dublin. School of Law. Discipline of Law, 2022)
Prison oversight is regarded by penology scholars as an essential means by which human rights and humane conditions in prison are upheld. However, despite significant growth in the number of oversight bodies in Ireland, significant issues regarding prison conditions and the treatment of people in prison still persist. In understanding prison oversight, prison managers present a key cohort for study; they are an essential conduit by which the human rights principles espoused by these mechanisms are translated to the prison environment. Drawing on the regulation and accountability literature as a theoretical framework, this research offers insight as to why engagement and compliance can vary. At the centre of this study is an empirical exploration of the accountability culture within the Irish Prison Service as well as prison managers experiences with three human rights-led oversight mechanisms the Office of the Inspector of Prisons (OIP), the Committee for the Prevention of Torture (CPT), and the prisoner complaints system. Interviews (n = 35) and surveys (n = 369) were used to explore prison managers experiences of accountability and their attitudes towards these three mechanisms. The analysis provides insight into what it is like to experience accountability as a senior member of the Irish Prison Service and how perceptions of accountability are shaped by prison as a work environment. The findings reveal complex, variegated and highly individualised attitudes towards mechanisms of oversight, with varying degrees of motivation to engage. The implications of this research are explored with respect to understandings of the wider prison culture and understandings of human rights-based prison oversight. Recommendations are posed for improvements to the oversight and future avenues for research in this area are identified.
APPROVED
Keywords: prison research; prison staff; accountability; oversight; inspection; monitoring; complaint; organisational culture